2020
DOI: 10.1016/j.jmmm.2020.167018
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the metamagnetic transitions in Y1−Er Fe2(H,D)4.2 compounds

Abstract: The structural and magnetic properties of Y1-xErxFe2 intermetallic compounds and their hydrides and deuterides Y1-xErxFe2H(D)4.2 have been investigated using X-ray diffraction and magnetic measurements under static and pulsed magnetic field up to 60 T. The intermetallics crystallize in the C15 cubic structure (Fd-3m space group), whereas corresponding hydrides and deuterides crystallize in a monoclinic structure (Pc space group). All compounds display a linear decrease of the unit cell volume versus Er concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…YFe2Hx hydrides were also studied for their magnetic and magnetocaloric properties especially around 4.2 H/f.u., where a ferromagnetic-antiferromagnetic (FM-AFM) transition with an itinerant electron metamagnetic (IEM) character has been observed [20,21,28,29]. This magnetic transition is accompanied by a cell volume variation and is sensitive to any cell volume change induced by an applied external pressure [30,31], D for H isotopic substitution [32,33] or R for Y substitution [34][35][36][37]. For example, the investigation of the monoclinic Y0.9Gd0.1Fe2(H1-zDz)4.2 compounds indicated that upon H for D substitution the FM-AFM transition temperature is shifted to higher temperature, whereas TO-D is shifted to lower value [38].…”
Section: Introductionmentioning
confidence: 99%
“…YFe2Hx hydrides were also studied for their magnetic and magnetocaloric properties especially around 4.2 H/f.u., where a ferromagnetic-antiferromagnetic (FM-AFM) transition with an itinerant electron metamagnetic (IEM) character has been observed [20,21,28,29]. This magnetic transition is accompanied by a cell volume variation and is sensitive to any cell volume change induced by an applied external pressure [30,31], D for H isotopic substitution [32,33] or R for Y substitution [34][35][36][37]. For example, the investigation of the monoclinic Y0.9Gd0.1Fe2(H1-zDz)4.2 compounds indicated that upon H for D substitution the FM-AFM transition temperature is shifted to higher temperature, whereas TO-D is shifted to lower value [38].…”
Section: Introductionmentioning
confidence: 99%
“…One more, such behavior supports the interest of more systematic magnetic characterizations of the RTM 2 series of Laves type compounds, with R being a heavy rare earth metal and TM being a solution of magnetic 3d metals. Otherwise, a structure spacer, such as inserted hydrogen atoms, might be of interest to modify i.e., the DOS in the vicinity of E F and then the magnetic couplings and configurations, as already mentioned here above [29,35,[44][45][46]67].…”
Section: Discussionmentioning
confidence: 86%
“…should be considered to detail the magnetic properties of the Er(Fe 1−x (Co-Mn) x ) 2 series. However, the concluding statements found in [67], as well as several refs herein mentioned, are of interest, since focusing on a meta-magnetic process is related to an itinerant electron meta-magnetic behavior of the Fe(TM) sublattice and corresponding to peculiarities (or changes) of DOS at the Fe Fermi level.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A value of magnetic entropy variation (ΔSM) close to that of Gd has been observed in monoclinic YFe2D4.2 and YFe2H4.2 around TFM-AFM = 84 K and 131 K respectively due to the itinerant electron metamagnetic (IEM) behavior of the Fe sublattice [28]. TFM-AFM is highly sensitive to any volume change induced by applying an external pressure [29], H for D isotope substitution [30] or chemical substitution of Y by another rare earth element (R = Gd, Tb, Er) [31][32][33][34]. To observe an MCE effect close to room temperature, we have undertaken a more systematic study of the influence of the chemical substitution for hydrides and deuterides with concentration near 4.2 H(D)/f.u..…”
Section: -Introductionmentioning
confidence: 99%